Pre-dispersal seed predation in Primula veris: among-population variation in damage intensity and selection on flower number - Leimu, R; Syrjanen, K; Ehrlen, J; Lehtila, K (2002)
The geographic mosaic theory of co-evolution states that evolution of interactions is driven by geographical variation in interactions between species. We investigated whether the intensity of pre-dispersal seed predation differed among nine Primula veris populations over 5 years, and whether such differences lead to geographical variation in selection on flower number. Seed predation intensity differed significantly among years and populations, and it increased with canopy closure and decreased with the density of the field layer vegetation. Individuals in open habitats also produced the highest number of flowers. Moreover, the phenotypic selection on flower number differed among years and populations. In populations of closed habitats, with high seed predation pressure, the increased number of flowers was often correlated with an increased number of damaged capsules. However, an increased flower number did not result in fewer intact fruits due to seed predation in any population.